2022
DOI: 10.3390/jcm11236881
|View full text |Cite
|
Sign up to set email alerts
|

Association of Proton Pump Inhibitor Prophylaxis on Clinical Outcome in Acute Ischemic Stroke in China: A Multicenter Retrospective Cohort Study

Abstract: Background: Overtreatment with proton pump inhibitors (PPIs) in acute ischemic stroke (AIS) patients continues to grow. We aimed to investigate the frequency of PPI prophylaxis without an appropriate indication in AIS patients in China and clarify the association between PPI prophylaxis and long-term prognosis. Methods: Based on a multicenter stroke registry database, neurological outcomes, stroke events, recurrent ischemic strokes, and all-cause death were compared between patients with and without PPI prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…PPIs, H2 receptor antagonists (H2RA) and mucoprotective agents are often used to manage post-stroke heartburn symptoms or prevent gastroduodenal injury. However, the long-term use of PPIs and H2RA has been associated with unfavorable outcomes [ 6 , 51 ]. Recent studies have demonstrated that the clinically used PPIs, including omeprazole, lansoprazole, and rabeprazole, act as ligands for ChAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPIs, H2 receptor antagonists (H2RA) and mucoprotective agents are often used to manage post-stroke heartburn symptoms or prevent gastroduodenal injury. However, the long-term use of PPIs and H2RA has been associated with unfavorable outcomes [ 6 , 51 ]. Recent studies have demonstrated that the clinically used PPIs, including omeprazole, lansoprazole, and rabeprazole, act as ligands for ChAT.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antiplatelet medications in the acute phase of ischemic stroke can increase the risk of gastrointestinal bleeding [ 5 ], necessitating the careful use of gastric mucosal protective drugs. However, a multicenter retrospective study involving 4542 patients with acute ischemic stroke has revealed that 73.4 % of the patients who received proton pump inhibitors (PPIs) for either prevention or treatment had poor long-term outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%